Learn to weave with Anne Field : a project-based approach to weaving basics - Field, Anne (Trafalgar Square Books, 2014)
Taking a project-based approach and with a well-founded understanding of the complexities of her craft, Anne deftly guides learners through the essential weaving techniques. Basic information on types of looms and what each is best suited for, how to thread or warp the loom and getting underway is followed by step-by-step instructions for 11 projects, including practical table runners, mats and cushion covers, wearable wraps, scarves, and a reversible jacket, through to a decorative wall hanging.